2018
DOI: 10.1007/s12094-018-1886-4
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeled F(ab′)2-cetuximab for theranostic purposes in colorectal and skin tumor-bearing mice models

Abstract: PurposeThis study aimed to investigate theranostic strategies in colorectal and skin cancer based on fragments of cetuximab, an anti-EGFR mAb, labeled with radionuclide with imaging and therapeutic properties, 111In and 177Lu, respectively.MethodsWe designed F(ab′)2-fragments of cetuximab radiolabeled with 111In and 177Lu. 111In-F(ab′)2-cetuximab tumor targeting and biodistribution were evaluated by SPECT in BalbC nude mice bearing primary colorectal tumors. The efficacy of 111In-F(ab′)2-cetuximab to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Cetuximab, another anti-EGFR antibody was digested to a Fab 2 and labeled with 111 In in two different studies and tested for theranostic properties. Imaging with 111 In-labeled Fab 2 showed accumulation in the tumor that peaked at 24 h post injection 17 , 18 . Two other studies using 64 Cu-cetuximab Fab 2 only reported images at 24 h and showed the ability of the Fab 2 imaging probe to monitor treatment 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Cetuximab, another anti-EGFR antibody was digested to a Fab 2 and labeled with 111 In in two different studies and tested for theranostic properties. Imaging with 111 In-labeled Fab 2 showed accumulation in the tumor that peaked at 24 h post injection 17 , 18 . Two other studies using 64 Cu-cetuximab Fab 2 only reported images at 24 h and showed the ability of the Fab 2 imaging probe to monitor treatment 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Approved radiolabeled mAbs and their derivatives Currently, two radiolabeled anti-CD20 murine mAbs, 90 Y-ibritumomab tiuxetan (Zevalin) and 131 I-tositumomab (Bexxar) have been approved by the United States Food and Drug Administration (FDA) for the treatment of relapsed or refractory, low-grade or follicular B cell Non-Hodgkin lymphoma (NHL), including rituximab refractory follicular NHL in 2002 and 2003, respectively [28]. 131 I-Metuximab for the treatment of hepatocellular carcinoma (HCC) and 131 I-chTNT for the treatment of lung cancer have been approved by the China National Medical Products Administration [29,30]. Clinical translation of radiolabeled antibodies therapy began with the approval of Zevalin and Bexxar.…”
Section: Radiolabeled Antibodies In Cancer Therapymentioning
confidence: 99%
“…TKIs, mAb and SMI have previously been radiolabeled for diagnostic purposes, some also for use in TRT, with progress in the field of epidermal growth factor receptor (EGFR) radio-immunotherapy (RIT) [ 23 , 27 , 28 , 49 , 50 , 51 , 52 ]. For instance [ 188 Re]Re-nimotuzumab and [ 125 I]iodo-mAb 425 are in a clinical stage for GB and [ 177 Lu]Lu]-/[ 211 At]At-L8A4 (EGFRIII) mAb and [ 177 Lu]Lu-cetuximab are in a preclinical stage for GB [ 37 , 53 , 54 , 55 , 56 , 57 , 58 ]. In addition, RTK signaling is affected by ionizing radiation and hence the combination of TKI and RT (external beam radiation therapy or TRT) could have synergistic effects [ 59 ].…”
Section: Nuclear Molecular Imaging and Trt Using Tkismentioning
confidence: 99%